Amplifying the Patient Voice: A Survey of Practitioners' Use of Patient-reported Outcome Measures Across Radiotherapy Providers in England. Issue 3 (March 2023) - Oliver, L.A.; Hutton, D.P.; Hall, T.; Cain, M.; Bates, M.; Cree, A.; Mullen, E.
Abstract: Aims: The NHS England Radiotherapy Service Specification calls for routine use of patient-reported outcome measures (PROMs). However, barriers exist at patient, healthcare professional and service levels. The aim of the present study was to determine the current use of PROMs within radiotherapy services in England. The current attitudes, barriers and enablers to the implementation of PROMs in radiotherapy practice were evaluated and practical recommendations to inform future implementation were developed. Materials and methods: A mixed-methods approach was adopted to obtain quantitative and qualitative data. An online questionnaire was developed and disseminated to all radiotherapy operational delivery network managers across England. The questionnaire consisted of 12 open and closed questions relating to PROMs use, with the option to provide free-text responses. Inductive thematic analysis was conducted on free-text comments, whereas descriptive statistics were used to analyse quantitative data. Results: In total, 182 responses were received from 40 of the 50 radiotherapy providers, resulting in a response rate of 84%. The current use of PROMs was analysed, including rationale for use, tools used, format of PROMs collection and timing within the radiotherapy pathway. Most respondents indicated that PROMs were used in the context of clinical trials only. Through thematic analysis, four identical key themes were identified relating to both barriers and enablers to PROMs use; these included IT infrastructure, time, human/financial resources and training/education. A fifth theme, standardisation, was identified as a key enabler to PROMs use. Conclusions: Our findings show that outside of clinical trials, PROMs are not routinely used in radiotherapy services due to barriers identified at professional and service levels. Here we provide recommendations to mitigate the barriers identified and implement PROMs in radiotherapy, including training for healthcare professionals and standardisation of PROMs tools and storage. This study provides a key first step in driving PROMs implementation within radiotherapy services across England. Highlights: Outside of clinical trials, PROMs were not widely used within radiotherapy services. Common PROMs used included QOL, anxiety/depression and urinary/bowel function tools. PROMs are completed using either paper or electronic forms, by staff or patients. Barriers include IT infrastructure, time, resources (staff/finances) and training. Enablers included IT, time, resources, training and standardisation.